2021
DOI: 10.1177/01461672211062401
|View full text |Cite
|
Sign up to set email alerts
|

Turning Tables: Offenders Feel Like “Victims” When Victims Withhold Forgiveness

Abstract: When offenders apologize to victims for a wrongdoing, they often expect forgiveness in return. Sometimes, however, victims may withhold forgiveness. Across four experimental studies, we find that offenders feel like “victims” when victims respond to their apologies with non-forgiveness. This can be explained by the fact that they interpret non-forgiveness as both a norm violation and a threat to their sense of power. Together, these mechanisms can account for the relationship between non-forgiveness and negati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Apology rejection can exacerbate the perceived loss of power, as control remains with the victims and the risk of renewed rejection persists. This idea is also mirrored in research by Thai et al (2023), who found that perpetrators felt threatened in their sense of power when victims responded with nonforgiveness to their interpersonal apology. Paralleling our prediction regarding the power of the victim group, we thus hypothesize that the perpetrator group's vulnerability to the victim group's response will also be visible to uninvolved third parties in the context of intergroup apologies.…”
Section: Rejecting An Apology: Effects On Third-party Perceptions Of ...mentioning
confidence: 68%
See 1 more Smart Citation
“…Apology rejection can exacerbate the perceived loss of power, as control remains with the victims and the risk of renewed rejection persists. This idea is also mirrored in research by Thai et al (2023), who found that perpetrators felt threatened in their sense of power when victims responded with nonforgiveness to their interpersonal apology. Paralleling our prediction regarding the power of the victim group, we thus hypothesize that the perpetrator group's vulnerability to the victim group's response will also be visible to uninvolved third parties in the context of intergroup apologies.…”
Section: Rejecting An Apology: Effects On Third-party Perceptions Of ...mentioning
confidence: 68%
“…Hence, rejecting an apology, and thus standing in the way of social harmony, can represent a deviation from a socially ingrained script (Darby & Schlenker, 1989). In fact, perpetrators-for whom the acceptance of the apology might be particularly relevant as it helps restore their impaired need for moral belonging (Shnabel & Nadler, 2008)-perceive the rejection of their apology as an illegitimate norm violation, leading to negative emotions toward the victims, as indicated by research on both interpersonal (Chiles & Roloff, 2014;Dhami, 2016;Thai et al, 2023) and intergroup apologies (Harth et al, 2011;Zaiser & Giner-Sorolla, 2013).…”
Section: Rejecting An Apology: Effects On Third-party Perceptions Of ...mentioning
confidence: 99%
“…Parties involved in a transgression often seek to reconcile with one another and repair the relationship. Victim forgiveness and offender self-forgiveness are important components within the reconciliation process, as each party comes to terms with the offense and attempts to move forward (e.g., Fincham et al, 2007; Pelucchi et al, 2013; Thai et al, 2021; Wenzel & Okimoto, 2010; Woodyatt & Wenzel, 2013). Thus, researchers have attempted to elucidate the mechanisms through which forgiveness and self-forgiveness can be facilitated (e.g., Strelan et al, 2017; Woodyatt et al, 2017).…”
Section: Co-rumination In Dyadic Relationshipsmentioning
confidence: 99%
“…Parties involved in a transgression often seek to reconcile with one another and repair the relationship. Victim forgiveness and offender self-forgiveness are important components within the reconciliation process, as each party comes to terms with the offense and attempts to move forward (e.g., Fincham et al, 2007;Pelucchi et al, 2013;Thai et al, 2021;Wohl et al, 2010;Woodyatt & Wenzel, 2013). Thus, researchers have attempted to elucidate the mechanisms through which forgiveness and selfforgiveness can be facilitated (e.g., Strelan et al, 2016, Woodyatt et al, 2017.…”
Section: Transgression-related Co-rumination: Scale Validation and Pr...mentioning
confidence: 99%